PELAKSANAAN TANGGUNG JAWAB PERUSAHAAN TERHADAP PENERAPAN KETENTUAN WAKTU KERJA BAGI PEKERJA/ BURUH PEREMPUAN HARIAN LEPAS PADA PT EWAN SUPER WOOD KOTA PEKANBARU - DENNY PRANATA AJIE; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Recognizing the importance of worker/laborer for companies,governments and the public, it needs to be thought that the workers/laborers cankeep their safety in carrying out the work. Generally, the workers/laborersindividually in a weak position in the fight for their rights. Still many are notimplemented in practice the protection of the rights of workers/laborers,especially the rights of female workers/laborers. Regarding the rights ofworkers/laborers of course strongly related to working time arrangements, as inthe work with the necessary guidelines concerning the maximum working timeprovision for workers/laborers especially those who work at night.The purpose of this study was to determine the form of the implementationof the implementation of corporate responsibility towards the application of theworking time of female workers/laborers casual, to determine the factors thatcause has not been implementation of corporate responsibility towards theapplication of the working time for female workers/laborers casual and to knowthe effort conducted by PT Ewan Super Wood in carrying out its responsibility tothe application of the working time for female workers/laborers casual.From the research there are three main issues that can be inferred. First,the implementation of corporate responsibility with respect to time by theworkers/laborers female casual PT Ewan Super Wood in Pekanbaru not inaccordance with the provisions of the labor time has been set in Article 77paragraph (1) and (2) of Law Number 13 Year 2003 on Employment. Second, thefactors causing PT Ewan Super Wood has not carried out its responsibility towork hours for female workers/laborers casual is due to the availability of alimited production, distribution of production time for 24 hours per day, lack ofknowledge and legal awareness of workers/laborers and not implementation shallreport to the Department of Labor. Third, efforts made by PT Ewan Super Woodis a reward every 2 weeks working days, apply the division of labor time in twoshifts working time and provide social security to workers/laborers casual. Advicewriter, expected PT. Ewan Super Wood more attention to the rights prescribed bythe Employment Act, especially in the application of the working time and must beactively coordination between the Department of Labor Pekanbaru supervisoryagency with the company in this case is PT Ewan Super Wood.Keywords: Corporate Responsibility - Provision of Work Hours - femaleworkers/laborers casual